Ekwiwalencja polskich czasowników przyjechać, dojechać, zajechać i czasowników rosyjskich приехать, доехать, заехать - Styrcz-Przebinda, Leokadia (Przegląd Rusycystyczny, 2009)
EQUIVALENCY POLISH VERBS PRZYJECHAĆ, DOJECHAĆ, ZAJECHAĆ AND RUSSIAN VERBS ПРИЕХАТЬ, ДОЕХАТЬ, ЗАЕХАТЬ Summary The article deals with three verbs — zajechać, dojechać and przyjechać — in Polish and Russian. The meaning, syntax and — partially — word-formational character is concerned here. Although the mentioned verbs seem to be very similar in both of the languages, the meaning is not totally the same. As for Polish, in some cases they can be used alternatively in specifi c syntactic contexts. In Russian, however, this concerns only two of those: приехать and доехать. It’s also distinctive here that заехать does not have the basic meaning of reaching the border.The work indicates as well ways of expressing that same meaning in other Slavonic lan-guages, those that are more similar to Western ones. Polish and Russian language are analyzed more precisely concerning meanings created by prefi xes in verbs dealing with move. The way of describing these verbs in dictionaries has also been included. ЭКВИВАЛЕНТНОСТЬ ПОЛЬСКИХ ГЛАГОЛОВ PRZYJECHAĆ, DOJECHAĆ, ZAJECHAĆ И РУССКИХ ГЛАГОЛОВ ПРИЕХАТЬ, ДОЕХАТЬ, ЗАЕХАТЬ Резюме В статье рассматривается эквивалентность глаголов движения: приехать, доехать, заехать в русском и польском языках. Несмотря на внешюю схожесть в контекстном упо треблении обнаруживаются существенные различия в лексическом значении приведeнных глаголов. Они отчасти вытекают из различий в морфологической и син-таксической структуре русского и польского языков. Кроме того прагматический ас-пект употребления глагола заехать обусловливает существование значительно больее развитой системы семантических связи в русском языке по сравнении с польским языком. Особое внимание посвящается лексикографической разработке приведeнных глаголов.